Hubungan Antara Perilaku Imitasi Dengan Konsep Diri Peserta Didik Di SMA Negeri 4 Sijunjung - Suryani, Wiwin Okta; Chandra, Yasrial; Solina, Wira (JURNAL MANAJEMEN PENDIDIKAN, 2025)
THE RELATIONSHIP BETWEEN IMITATION BEHAVIOR AND SELF-CONCEPT OF STUDENTS AT STATE SENIOR HIGH SCHOOL 4 SIJUNJUNGAbstract.  This research is motivated by the existence of students who have low self-concept, students who feel embarrassed to appear in front of the class, students who are less able to interact with their surroundings, students who do not know their own abilities, so that students do not want to develop their potential. This research aims to describe 1) students' self-concept. 2) students' imitation behavior. 3) the relationship between imitation behavior and students' self-concept at SMA Negeri 4 Sijunjung. This study uses a correlational quantitative research method, with a population of 182 people, a Simple Random Sampling technique with a sample size of 124 people. The instrument used in this study is a questionnaire. Data analysis in this study is percentage and product moment correlation. The results of this study indicate 1) the description of the self-concept of students at SMA Negeri 4 Sijunjung is in the fairly high category, 2) the description of the imitation behavior of students at SMA Negeri 4 Sijunjung is in the good category, 3) significant relationship between imitation behavior and self-concept of students at SMA Negeri 4 Sijunjung in other words the hypothesis is accepted that there is a relationship between imitation behavior and self-concept. For this reason, it is recommended that BK teachers can provide special assistance to help students build a better self-concept